Desenvolvimento de um modelo para plataforma de gerenciamento e execução de obras - Zanuto, Geisimara (2022)
In Brazil, the construction industry is a segment in constant economic development. With the increase in demand and competitiveness in the market, the search for investment in management, application of news materials and technologies grows, in order to improve performance, increase productivity and the quality of the final product, since the lack of planning in construction causes unforeseen events that can generate rework, waste of materials, increase in costs and execution time. Currently, the construction industry has digital tools are little used due to the cost and complexity of the platforms on the market. With based on these data, it was proposed a model for a platform for management and execution of works, composed of tools for registering customers, employees, suppliers and service providers, tools for inventory control, with the objective of registering and monitor input and output of inputs, issue reports for stock checking and purchase order, and finally tools or controlling works, consisting of, work registration, service contracts, technical responsibility records, projects, descriptive memorandum, budget, schedule, daily work report and photographic report. The model was developed with the purpose of promoting the user experience from a prototype to enable its application in the market. In this way, the tools were designed with a focus on simplicity and usability, applied in an intuitive, practical and efficient way. It is concluded that the use of technology in construction can provide greater control and agility in the execution of activities, reducing costs and thus, minimizing risks and unforeseen events through strategic planning.